Placental Growth Factor Testing to Assess Women With Suspected Preeclampsia: A Multicentre, Pragmatic, Stepped-wedge Cluster-randomized Controlled Trial. Issue 1 (March 2020) - Duhig, K.E.; Myers, J.; Seed, P.T.; Sparkes, J.; Lowe, J.; Hunter, R.M.; Shennan, A.H.; Chappell, L.C.
Abstract : ( Lancet . 2019;393:1807–1818) Approximately 3% of singleton pregnancies are affected by preeclampsia, which can be difficult to diagnose as many women are asymptomatic. Hypertension and increased urinary protein excretion are common factors used to establish the diagnosis, but there are challenges in testing and observing both of these features. The pathophysiology of preeclampsia involves angiogenic factors, and low circulating maternal placental growth factor (PlGF) concentrations have been found to be useful in the diagnosis of preeclampsia with high sensitivity and negative predictive value. However, this potential tool for diagnosing preeclampsia should first be tested in a real-world setting to understand both its practical benefits and challenges. This study aimed to determine whether a preeclampsia diagnosis could be more quickly reached in women with suspected preeclampsia by incorporating measurement of the PlGF circulating concentration into an already established clinical management algorithm. The study also investigated the effect of using this diagnostic approach on maternal and perinatal outcomes.